MANGROVE, EKOSISTEM PENYELAMAT LINGKUNGAN - Sulistyaningsih, Dian; P, Puryantoro; Warsiyah, Futriyatul (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
The destruction of mangrove Forest at the north coast of Java has been caused by land conversion. In Situbondo regency, the problem started from activities of the shrimp cultivation in the 1980 â 1990âs. There are three (3) major issues in Indonesian mangrove management, namely ecological, socioeconomic, and institutional. In the last two years, the beach abbration has reached 5 â 10 meters from shoreline. It used the serious management from Situbondo Government Regency, the society and stakeholder through the 1000 mangrove planting in the beach. The mangrove planting activities were started by the socialization of planning, planting, and handling mangrove trees. Three months after implementation of mangrove planting, the mangrove growth well along the beach. It caused by the coastal society supports.